Tourists’ Perception on Service Quality of a Resort in Tourism Area, Wayanad in Kerala A Case Study of Banasura Island Retreat - Rathi K. N (IRACST- International Journal of Research in Management & Technology (IJRMT), 2014)
Kerala is the southern state of India which providing more importance to tourism industry. The investigator intended to explore the area of tourism and the service quality in this sector. The main objective of this paper is to investigate tourists’ perceptions of services delivered by resort operators in Wayanad district, Kerala, India. The investigator used both qualitative and quantitative data for the study. A well structured questionnaire was prepared to analyse the response from different tourists stayed at Banasura Island Retreat, a resort at Wayanad. A face-to-face survey was conducted with thirty tourists who had stayed for at least one night at the resort. The result of the study that the tourists are perceived the service quality as good but it is below their expectation before the visit.